Enzymatic synthesis of dilaurylazelate ester for nanocosmeceutical application - Khairudin, Nurshafira (2018)
Azelaic acid (AzA) and its derivatives have been known to be effective in the treatment of acne and various cutaneous hyperpigmentary disorders for cosmeceutical application. Currently, azelaic acid is available in the market as a 20% azelaic acid cream for the treatment of acne, and has been approved for use by the Food and Drug Administration (FDA). However, high concentration (20%) of azelaic acid is needed to guarantee the drug availability in the skin, which caused an increase the incidence of side effects such as irritation, dryness, and redness of the skin associated with exposure to high levels of undissolved dispersed azelaic acid having an inherent low pH. A derivative of azelaic acid with even better characteristics than the original starting material may be produced through the modification to azelaic acid, especially the efficacy of a relatively low dosage of AzA derivatives in the treatment of acne. Dilaurylazelate ester was produced through the esterification of azelaic acid with lauryl alcohol using immobilized lipase B from Candida antarctica (Novozym 435). The chemical and physical characterization of dilaurylazelate ester was analyzed in order to be effectively applied in cosmeceutical application. The chemical characterization was determined by Fourier-Transform Infrared spectroscopy (FT-IR), Gas Chromatography Mass Spectroscopy (GCMS), and Nuclear Magnetic Resonance (NMR) in order to verify and elucidate the structure of product. The normal fibroblasts cell line (3T3) was used to assess the cytotoxicity of dilaurylazelate ester and the antibacterial activity against the pathogen bacteria Propionibacterium acnes ATCC 11827 was studied. Response surface methodology (RSM) and artificial neural network (ANN) were used to optimize and predict various performance parameters of the enzymatic reaction conditions, namely enzyme amount, reaction time, reaction temperature and molar ratio of substrates that could affect on the degree of percentage conversion of dilaurylazelate ester. The optimization ...